(untitled) (Journal of the College of Basic Education, 2022)
The Arabic sources mentioned that the Arabic calligraphy which ended up in the Nabataeans through the Nabataeans came in several names, including the Anbarian line, the Bahri line, the civil line and the Makki line. All the lines defined by the Arabs before Islam and derived from the line of the Nabataeans, and then knew the visual line and the Kufic line and the two lines known by the Arabs after Islam. And it is likely that the naming of the lines with the names of the cities that it was the result that the Arabs who were ignorant of writing before Islam received these lines with the goods rolled Vzmha the names of the bodies received from them We have mentioned that the calligraphy before the era of prophecy was known Nabataean line because he came to the land of the Arabs of The land of Nabat, and the end of the line to Mecca and the city known by their names and then called the whole region where he was known later (Hijaz font). Although we know the types of these lines, we can not attribute them to the time because we did not find examples of them dated in the exception of a few models of the Hijaz line and if it was common in the writing of the Koran, the line is a line Mbesut originated in Iraq, which was It combines the drought and softness closer to the quadrature and angles, used in the writing of the major sources until replaced by the copy line created by Ibn Mqla and the quality of the son of the doorman and Almstasmi At this stage and this development used these types of lines in the general written purposes without the Koran and Whose name came with a sophisticated probe or in the editorial line that was used This is the line that has been clearly improved by the son of Makla and the son of the doorman. And if the subject of our mission is looking at the effect of the effects of Ibn Mqla who drew his hand and is the letter of science font and pen, which added beauty to the writing, despite the focus on the engineering inventory in the drawing format, I mean that measurement and ratios in the relationship of one character to another and despite the This description, however, that the line of the son of a pole was hit in the ideals. Al-Thala’bi described it as saying, "It is a good example, because it is the best line of the world, and what is the view of the opinioners, but what the narrators narrated, such as its rise from description and the course of magic." Therefore, Baghdad was the center of all these developments, which we mentioned over the five centuries from the son of a cousin to Jamal al-Din Yaqoot Ibn Abdullah al-Mustassmi, who lived in the era of the last Abbasid Caliphs, who died in 698 AH and who was known as the calligrapher’s last calligrapher Baghdadi calligraphers to play an important role in the development The Arabic calligraphy and tajweedh, adding on the line perfection and well made him a pioneer of those who came after the calligraphers and despite the greatness of sapphire in the line was the first Manhalh Ibn Mqlp and the son of the doorman, who attributed to them tenderness and agility and cut the pen, The subsequent generations of calligraphers should follow suit.